A path analytic model of health beliefs on the behavioral adoption of breast self-examination - Moey, Soo Foon; Che Mohamed, Norfariha; Lim, Bee Chiu (AIMS Press, 2020)
Background: In Malaysia, breast cancer accounted for 34.1% of all female cancer cases with women presenting breast cancer at late stages. Breast cancer has a higher five-year survival rate if detected early. An increase of approximately 30% in the five-year survival rate is indicated if breast cancer is detected at stage III compared to stage IV. Thus, the survival rate of breast cancer can be increased by creating awareness and encouraging breast cancer screening amongst women. Breast self-examination (BSE) is highly recommended for breast cancer screening due to its simplicity with no incurred cost. The Health Belief Model is used in this study to explain and predict the adoptive behaviour of BSE amongst women in Kuantan, Pahang. Materials and methods: This study employed a multi-stage sampling method using a simple proportion formula at 5% type 1 error, p < 0.05 and absolute error at 2% which resulted in a sample of 520 participants. The data for the study was obtained using a validated bilingual self-constructed questionnaire and the model constructed using Mplus software. Results: Perceived severity, benefits and barriers were found to significantly influence the behavioural adoption of BSE. Married women aged from 45 to 55 years and knowledge were found to significantly moderate the relationship between perceived benefits and behavioural adoption of BSE. Further, self-efficacy was found as the core construct that mediates the relationship between married women aged 45 to 55 years and the behavioural adoption of BSE. Conclusion: Self-efficacy is found in the study to influence the behavioural adoption of BSE. This is undeniable as self-efficacy can promote confidence in initiating and maintenance of behavioural change if the perceived change is beneficial at an acceptable cost.